Experimental test methods for the properties of building materials based on class "f" and "c" ash from a thermal power plant (Международный научный журнал «Инженер», 2026)
The article covers the analysis of the technology of recycling into building materials by using ash of classes F (fly ash) and C (bottom ash) emitted by thermal power plants. It also shows the analysis of the physicochemical properties of ash and slag, the directions of use in building materials and environmental effects. The results of the assessment of the significance of new technologies for increasing the efficiency of production of building materials from waste and minimizing their impact on the environment are presented.